Identifikasi Keragaman Genetik Gen Growth Hormon Receptor Dengan Enzim Restriksi Mbo Ii (Ghr|Mbo Ii) pada Sapi Bali - Made Sriasih; Maskur Maskur; Nurul Huda (Faculty of Animal Husbandry, University of Mataram, 2015)
Growth Hormone Receptor (GHR) gene is a member of the super familycytokine/hematopoietin receptor. GHR plays a role in mediating the biological activity of growth hormone on target cells that lead to the affection of the nature ofgrowth in beef cattle carcasses and the nature of milk production in dairy cows. This study was designed to identify the genetic diversity of GHR genes exon 10 in Bali cattle. Genotype variation of gene candidates was identified using PCR-RFLP technique. The results showed that mutation at position of 755bp exon 10 of GHR gene as determined by Maskur (2012) can be identified using MBO II restriction enzymes at position of 125bp or at position of 282bp base nucleotidescaused by transition mutation of C/T and substitution of amino acid threonine to isoleucine.Genotype identification of GHR gene exon 10 resulted in three individual genotypes in Bali cattle population namely CC, TT and CT with frequency of 0.1931; 0.5455 and 0.2614respectively. The result of XÂ² test and heterozygosity observationas well as heterozygosity expectation indicate that the genotypedistribution on Bali cattle population in this study were not in Hardy-Weinberg equilibrium (Hardy-Weinberg Equilibrium/ HWE). The value of GHR|MBO II gene Polymorphic Informative Content was 0.342051, might be used for genetic identifier, and was quite informative as gene identifier for linkage analysis in the population.